2018
DOI: 10.3390/ijms19061626
|View full text |Cite
|
Sign up to set email alerts
|

Oxaloacetate Ameliorates Chemical Liver Injury via Oxidative Stress Reduction and Enhancement of Bioenergetic Fluxes

Abstract: Chemical injury is partly due to free radical lipid peroxidation, which can induce oxidative stress and produce a large number of reactive oxygen species (ROS). Oxaloacetic acid is an important intermediary in the tricarboxylic acid cycle (TCA cycle) and participates in metabolism and energy production. In our study, we found that oxaloacetate (OA) effectively alleviated liver injury which was induced by hydrogen peroxide (H2O2) in vitro and carbon tetrachloride (CCl4) in vivo. OA scavenged ROS, prevented oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Our previous study showed that urantide could effectively inhibit the MAPK signalling pathway in the tissues of atherosclerotic rats ( 10 ). Studies have revealed that urantide has antioxidant and anti-inflammatory effects and served a key role in CCl 4 -induced ALI ( 33 36 ). The present results indicated that, after 1 week of preventive urantide administration, the serum levels of ALT and AST did not increase significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that urantide could effectively inhibit the MAPK signalling pathway in the tissues of atherosclerotic rats ( 10 ). Studies have revealed that urantide has antioxidant and anti-inflammatory effects and served a key role in CCl 4 -induced ALI ( 33 36 ). The present results indicated that, after 1 week of preventive urantide administration, the serum levels of ALT and AST did not increase significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The higher ROS production can result in hepatocyte damage, and persistent accumulation of ROS leads to inflammation and release of TNF- α [100]. In HgCl 2 -induced liver injury, Hg 2+ gets tightly complexed with hydrosulphonyl moieties and depletes intracellular hydrosulphonyl moieties and leading to the generation of more ROS [86].…”
Section: Sirt1 Decreases the Inflammatory Responses In Dilimentioning
confidence: 99%
“…The TCA cycle is reported as the final common oxidation pathway of fat, carbohydrates, and amino acids, and is also the most important central pathway that connects almost all metabolic pathways of individuals [ 36 ]. In addition, the TCA cycle is closely related to some liver diseases.…”
Section: Discussionmentioning
confidence: 99%